(untitled) (International Journal of Food and Nutritional Sciences, 2021)
In ayurveda, Ahara (food) is considered Mahabhaishajya that is called to be the superior medicine and avoidance of the concept of Ahara in correcting the disorder can lead to the development of deformities resulting in several of pathological progression. Incompatible food practices can cause metabolic disturbances. Consideration for specific diet patterns and healthy lifestyles is quite evident in ayurveda in various contexts of diseases aiming at nullifying the aggravated doshas as well as the curative aspects of disease Rheumatoid arthritis is a systemic autoimmune disease, considered the most common inflammatory articular disease among the general population. The clinical presentation of Amavata closely mimics the unique variety of Rheumatological disorders called Rheumatoid Arthritis. Rheumatoid arthritis is a chronic inflammatory disorder that affects the joints, with an estimated prevalence of 0.7% in India. The present study aims to review the concept of ahara dravya in terms of Dietary regimen called as pathyapathya in the presentations and prevention of Amavata, the concept of pathyapathya in amavata were collected from various classical Ayurvedic works of literature along with the available commentaries and various scientific publications and were thoroughly analysed to establish a relation between the pathyapathya explained and their role in breaking the pathogenesis.